2022
DOI: 10.1007/s40152-022-00279-w
|View full text |Cite
|
Sign up to set email alerts
|

Market women’s skills, constraints, and agency in supplying affordable, safe, and high-quality fish in Ghana

Abstract: In Ghana, the role of female informal traders (“market women”) in making low-cost smoked and dried fish available in urban and rural marketplaces is the key to explaining the high consumption of fish in the country. However, market women’s contribution to food security and nutrition (FSN), as well as to fish quality and safety is underrated and poorly understood. Fish marketing requires proficient distribution and preservation skills, economic and sociocultural competence, and a high degree of mobility. Fish t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…This study demonstrates how the diverse forms of marginalisation impact urban coastal fishing actors’ access to meaningful livelihoods in Ghana. This has potential impacts on food security because fish traders in coastal communities distribute fish products to large metropolitan markets in Ghana and other neighbouring nations (Ayilu & Niawung, 2022 ; Overå et al, 2022 ). In answering the question of how accumulation by dispossession and securitisation shapes urban coastal fishing livelihoods in Ghana, this study makes three contributions.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates how the diverse forms of marginalisation impact urban coastal fishing actors’ access to meaningful livelihoods in Ghana. This has potential impacts on food security because fish traders in coastal communities distribute fish products to large metropolitan markets in Ghana and other neighbouring nations (Ayilu & Niawung, 2022 ; Overå et al, 2022 ). In answering the question of how accumulation by dispossession and securitisation shapes urban coastal fishing livelihoods in Ghana, this study makes three contributions.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining elements under social factors, namely inclusion approach, health and food safety programmes, evaluation and feedback scheme, insurance schemes and contingency and working timeline are unique to this study. Inclusion approach focussing on women integration is widely reported in Ghana's capture fisheries sector (Ameyaw et al, 2020;FAO, 2023;Golo and Erinosho, 2023;Overå et al, 2022), as compared to aquaculture. This suggests the need to create awareness on mainstreaming women into Ghana's aquaculture industry.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to houseflies and pathogenic insects may have influenced the favorable response toward using insecticides during fruit and vegetable handling. Overå et al [ 41 ] identified the spraying of insecticides to control houseflies and insects by fishmongers in local markets in Ghana. Indeed, the local market settings of low environmental and sanitary standards contribute to the difficulty of maintaining and sustaining food hygiene and safety practices.…”
Section: Discussionmentioning
confidence: 99%